Protecting whistle-blowers in the public service: A global survey of whistle-blowing laws applicable to the public service sector - Maximilien Roche (International Labour Organization (ILO), 2025)
This paper provides an analysis of national laws relevant to whistle-blowers in the public sector across 67 ILO Member States. It studies each national law through a selection of indicators derived from reference frameworks and guidance by inter-governmental organizations (e.g. UNODC, OECD) and global civil society organizations (e.g. Transparency International, the International Bar Association). It aims at drawing a picture of each studied member state's approach to specific questions such as which public sector employees should benefit from a statutory whistle-blower protection, under which conditions and what such protection entails. The study concludes by observing that although enacting national laws protecting whistle-blowers is a relatively recent trend, such laws present a broad diversity of approaches which contrasts with the relative consistency of institutional recommendations.
Keywords: 330